2002
DOI: 10.1034/j.1600-0463.2002.11007807.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro susceptibility ofStaphylococcus aureustowards amoxycillin‐clavulanic acid, penicillin‐clavulanic acid, dicloxacillin and cefuroxime

Abstract: Sixty-three Staphylococcus aureus isolates with a wide distribution in quantitative beta-lactamase production were tested in vitro against amoxycillin and penicillin in combination with clavulanic acid to establish the influence of total amount of beta-lactamase present on the ability of clavulanic acid to protect against beta-lactamase degradation. The beta-lactamase stability of cefuroxime and dicloxacillin was also evaluated. MIC was determined by agar dilution using Mueller-Hinton agar with both a conventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The relative stabilities of cefuroxime have been previously described, although using few Bla-positive strains of unknown type (18). Cefuroxime has shown similar efficacies to methicillin and cefazolin in the treatment of experimental MSSA endocarditis (19) and appeared to have greater efficacy than cefazolin in an endocarditis model using an MSSA strain with high-level production of type A Bla (20).…”
mentioning
confidence: 99%
“…The relative stabilities of cefuroxime have been previously described, although using few Bla-positive strains of unknown type (18). Cefuroxime has shown similar efficacies to methicillin and cefazolin in the treatment of experimental MSSA endocarditis (19) and appeared to have greater efficacy than cefazolin in an endocarditis model using an MSSA strain with high-level production of type A Bla (20).…”
mentioning
confidence: 99%
“…36 Recently, scientists observed that clavulanic acid was highly effective in protecting against beta-lactamase degradation of both penicillin and amoxicillin and found that both cefuroxime and dicloxacillin were highly stable against staphylococcal beta-lactamase degradation. 37 However, these novel approaches are still under development and long-term effects have not been studied.…”
Section: Need Of New Therapiesmentioning
confidence: 99%